2012
DOI: 10.1002/term.1619
|View full text |Cite
|
Sign up to set email alerts
|

Implantation of osteogenic differentiated donor mesenchymal stem cells causes recruitment of host cells

Abstract: The interaction between host and donor cells is believed to play an important role in osteogenesis. However, it is still unclear how donor osteogenic cells behave and interact with host cells in vivo. The purpose of this study was to track the interactions between transplanted osteogenic cells and host cells during osteogenesis. In vitro migration assay was carried out to investigate the ability of osteogenic differentiated human mesenchymal stem cells (O-hMSCs) to recruit MSCs. At the in vivo level, O-hMSCs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…For wound healing, the mobilization and homing of endogenous MSCs to the injured tissue is an essential but extremely complex process, and the molecular mechanisms are almost unknown [3,4]. In the present study, we demonstrated that cultured hBMSCs exhibited a potent capacity of attracting hBMSCs by secreting soluble chemokines, which was consistent with previous in vivo studies [3,6,7]. Such chemotactic power was comparable to that elicited by IL-1β, IL-6, and TNF-α, further validating the paracrine effects of transplanted MSCs.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…For wound healing, the mobilization and homing of endogenous MSCs to the injured tissue is an essential but extremely complex process, and the molecular mechanisms are almost unknown [3,4]. In the present study, we demonstrated that cultured hBMSCs exhibited a potent capacity of attracting hBMSCs by secreting soluble chemokines, which was consistent with previous in vivo studies [3,6,7]. Such chemotactic power was comparable to that elicited by IL-1β, IL-6, and TNF-α, further validating the paracrine effects of transplanted MSCs.…”
Section: Discussionsupporting
confidence: 81%
“…This notion is further reinforced by our previous findings that bone repair mediated by transplanted MSCs was largely attributed to the expansion and differentiation of endogenous MSCs [5]. Moreover, emerging new findings suggested that transplanted donor MSCs could recruit host stem/progenitor cells to the transplantation site for tissue repair [6,7]. These observations have kindled much interest in mechanisms governing host MSCs migration induced by transplanted MSCs.…”
Section: Introductionmentioning
confidence: 49%
See 1 more Smart Citation
“…Increased BV/TV may also result from an indirect effect of the transplanted cells on osteoblast differentiation as demonstrated by the upregulated expression of endogenous genes in transplanted oim that were associated with osteoblast differentiation, including Dmp1, Phex, and Bgn [48][49][50]. Others have also shown an effect of transplantation on endogenous osteoblast activity, for example, transplantation of osteogenic differentiated MSC in SCID mice resulted in increased bone being produced by host cells [66], and endogenous osteoblast numbers were increased after transplantation of term placental stem cells in a SCID-rab mouse model of medullary myeloma-associated bone loss [67]. We also showed upregulation in transplanted oim of endogenous chondrogenesis genes including chondrogenesis regulator Sox9 [38] and Runx2, implicated in chondrocyte maturation through Col10a1 transactivation [68].…”
Section: Discussionmentioning
confidence: 99%
“…The role of seed cells in the process of osteogenesis has been thought to stem from the proliferation and differentiation into osteoblasts by the seed cells on the tissue engineering bone to complete the bone repair [12][13][14][15]. However, recent studies showed that the seed cells contributed less to the later repaired tissues and most cells that participate into bone repair were derived from the host cells that had migrated to the site of injury to promote wound healing [13,[16][17][18].…”
Section: Introductionmentioning
confidence: 99%